Sailing Across the Atlantic: An Exploration of the Psychological Experience Using Arts-Based Research - Pipere, Anita; Mārtinsone, Kristīne; Regzdiņa-Pelēķe, Laura; Grišķeviča, Ingūna (Frontiers in Psychology, 2020)
The reported study pursues the bidimensional objective, namely, (1) to grasp the essence of the psychological experience of a transatlantic journey and (2) to observe the potential of arts-based research for the enhancement of the well-being of sailors. The sample consisted of three males and one female – Latvian citizens, aged 36–68 years, with higher education and different sailing experience. In the context of a case study grounded on arts-based research methods, the freehand drawings of self-portraits or something important during the day were obtained using individual diaries containing daily reports on the sailing experience. After the journey, individual drawings prompted interviews organized for each participant. The results were triangulated with data from the logbook. In their drawings, participants focused more on the environment rather than on self-representation, that is, telling the story about “here and now” in terms of specific time (journey), place (boat), and their relationship with nature, as well as dealing with problems during the trip. The psychological experience of transoceanic sailing matched the three general dimensions (dynamics, context, and content of experience) of the conceptual framework constructed for this study. The three dimensions of experience were equivalently represented in research data; however, only dynamics and context were fully delineated in all theoretical subcategories. As to the potential of arts-based research for the enhancement of sailors’ well-being, the findings show both direct and indirect evidence concerning their psychological and existential well-being. Further research is still needed to confirm the findings on a broader scale and in other contexts.